Strategi Pengajaran Bahasa Arab di Sekolah Dasar Islam Arrisalah - Sahana Anggian, Lutvi Ali (Mahira: Journal of Arabic Studies, 2021)
The achievement of the objectives of learning Arabic in Qiroah material cannot be separated from good planning and learning strategies. This study aims to determine how the Qiroah learning strategy in Arrislah Islamic Elementary School. The study used qualitative methods, with observation, interview and documentation techniques as data collection techniques, and Miles and Huberman's techniques, namely data reduction, data display and data verification as data analysis techniques. The strategy for teaching Arabic qiroah material at Arrisalah Islamic Elementary School has been going well. This is evidenced by the preparation of a good learning implementation plan, starting with the introduction, core activities and closing. In the planning, it has not been clearly described related to the strategies used in the teaching and learning process. However, the teacher has used the qiroah strategy when the learning process took place. Theoretically and practically this research is expected to contribute to schools and teachers in order to prepare lesson plans as well as possible, complete the components in planning the implementation of learning, and determine strategies, methods, approaches, and appropriate media for the subject matter to be delivered to students. students, so that the material becomes more easily absorbed and mastered by students and learning objectives can be achieved optimally